Indigenous and Quilombolas: protection of fundamental rights from the perspective of social policies in favor of vulnerable groups and jurisdictional action.” (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article will address the situation of Indigenous people and Quilombolas, as ethnic minorities, in the face of the Federal Constitution, using a qualitative, doctrinal and bibliographical methodology. In the scope of human rights, the rights of minorities are present in the discussions, mainly from the perspective of the Democratic State of Law, which ensures the ideals of justice, dignity and equality as supreme values. Currently, existing minorities are socially marginalized and their citizenship rights and access to fundamental rights are violated. In this attempt, the specific objectives to be discussed are: the Concept of Minorities; Minorities and Vulnerability; Fundamental Rights as the foundation of Minority Rights; Multiculturalism; Cultural Pluralism as the end of Assimilationism; Traditional Territories as an Instrument for the Preservation of Historical Heritage for Indigenous Peoples and Quilombolas; Public Policies and the Judicialization of Political Power and, finally, Public Policies and Traditional Communities. In effect, the Indigenous and the Quilombolas represent a significant portion of the social groups that contributed to the construction process of Brazilian society, suffered and, to a certain extent, still suffer discrimination in various ways. It can be seen, therefore, that Brazilian society, despite the significant progress represented by the enactment of the Federal Constitution of 1988, has not assimilated the dimension of the relevance of recognizing ethnic-cultural diversity, especially the need to reconcile respect for the cultural diversity of each people and the association between cultures without annihilation, through reciprocal cooperation. Finally, in view of humanity as a whole, the promotion of social justice is pursued, dignifying the condition of indigenous peoples and quilombolas as ethnic minorities,